Prospects of legal regulation of the space tourism in international space law - Кулієв, Ібрагім Орудж огли; Халілов, Зафіг (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The offers related to definition of main essence of legal regulation of space tourism in the international space law, the theoretical comments of current legal categories in this area and comparative analysis of interior state legislative acts, problems related to legal status of the space tourists and perspectives of legal regulation on above-said are stated in the article. Specific features of the outer space and its legal regime, the proximity of the space tourism and space, and many other features indicate that this type of tourism should be considered exactly in international space law. The legal regulation of the space tourism should be considered not in the Law on Tourism but in the Law on Space Activities.